Physiological Changes in the Elderly - Mutlay, Feyza (General Internal Medicine VI (Spring), 2024)
Advancements in medicine and science are leading to longer life expectancy. The physiological decline in organs and systems caused by aging makes it difficult to maintain homeostasis. The aging population worldwide poses challenges in healthcare, finances, and caregiving. It is essential to protect the health of elderly individuals and ensure they can participate in society as independent individuals. To prevent or delay chronic diseases and causes of disability, healthcare providers must first know the physiological changes in the elderly. In this chapter, we present general and specific characteristics of aged tissues/organs in many systems in the body associated with aging.